(untitled) (Olhares, 2025)
This article follows the traces of memory, understanding the performing body connected to the environment in which it lives, serving as a site of exploration where poetic events begin. It reports on some experiences from the political movement Art for Democracy, a tactical group that uses art as a language, always seeking collective propositions of multiple voices. Emphasizing the unexpected as one of the strategies for the symbolic occupation of spaces and the gathering of bodies to create images that dispute new narratives, it highlights the idea of the body as a territory capable of conjuring landscapes.